Carriage of Extended-Spectrum-β-Lactamase- and AmpC-β-Lactamase-Producing Enterobacteriaceae (ESBL-PE) in Healthy Community and Outpatient Department (OPD) Patients in Nepal - Dipendra Kumar Mandal; Shiv Kumar Sah; Shyam Kumar Mishra; Sangita Sharma; Hari Prasad Kattel; Sanjeet Pandit; Pranav Kumar Yadav; Ujjwal Laghu; Rajani Lama; Niranjan Prasad Sah; Jeevan Bahadur Sherchand; Keshav Parajuli; et al. (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. Extended-spectrum β-lactamase (ESBL)- and AmpC-β-lactamase-producing Enterobacteriaceae have recently emerged as a public threat in the treatment of nosocomial as well as community-acquired infections. Very little information is currently available about its existence in Nepal. We, therefore, aim to determine the prevalence of ESBL and AmpC-β-lactamase-producing Enterobacteriaceae and also to determine their drug resistance pattern. Methods. During a 6-month period (November 2014–April 2015), a total of 190 stool specimens from 190 participants were obtained from different population. Of the total 260 fecal isolates, 152 from outpatient department (OPD) and 108 from healthy volunteer were collected. Stool specimens were cultured and enterobacterial isolates were subjected to antimicrobial susceptibility tests according to the standard microbiologic guidelines. ESBL was screened using ceftazidime (CAZ, 30 μg) and cefotaxime (CTX, 30 μg) disks and confirmed by double-disk synergy test. AmpC-β-lactamase enzyme production was detected by the aminophenylboronic acid inhibitor-based detection method. Antibiotic susceptibility test was performed for ESBL-positive isolates as per the Kirby-Bauer disk diffusion method, and interpretation was done according to CLSI (Clinical and Laboratory Standard Institute). Results. The prevalence of ESBL, AmpC-β-lactamases, and coproducer (ESBL + AmpC-β-lactamase) producing Enterobacteriaceae in OPD participants were 30.92%, 18.4%, and 13.81%, respectively, while 25%, 6.4%, and 1.8% in healthy population. ESBL-producing E. coli was 70.2% followed by K. pneumoniae (12.7%), and among AmpC-β-lactamase producer, E. coli were detected in half of the isolates (14/28, 50.0%) among OPD patients. Similarly, E. coli remained the most frequent ESBL producers 21/27 (77.8%) followed by K. pneumoniae 4/27 (14.21%) in healthy participants, and K. pneumoniae 5/7 (71.42%) and C. freundii 2/7 (28.57%) were detected highest among AmpC-β-lactamase-producing isolates. All isolates were highly sensitive (100%) to imipenem in both OPD and healthy participants. Conclusion. Our study revealed a high prevalence of ESBL- and AmpC-β-lactamase-producing enteric pathogen in Nepalese OPD and healthy population. The significant increase of these isolates and increased rate of drug resistance indicates a serious threat that stress the need to implement the surveillance system and a proper control measure so as to limit the spread of ESBL-producing Enterobacteriaceae (ESBL-PE) in both OPD as well as in community. Therefore, healthcare providers need to be aware that ESBL- and AmpC-β-lactamase-producing strains are not only circulating in hospital environments but also in the community and should be dealt with accordingly.